PERILAKU TANAH EKSPANSIF YANG DITAMBAHKAN LAPISAN GEOTEXTILE TERHADAP DAYA DUKUNGNYA - Sutikno; Endang Kamdari (Politeknik Negeri Jakarta, 2023)
There are many problems regarding expansive soils, including the magnitude of stability (CBR) and swelling due to the compaction process, fluctuating water content. The compaction process is carried out layer by layer (field/laboratory), in accordance with the laboratory compaction process, layers of sand are given, so that the arrangement is alternate (5 layers). Each layer is given a membrane / sheet of geotextile. The conclusions obtained are: The amount of swelling in the compaction test with Modified Compaction in soaked conditions is 12.7%, this illustrates that the expansive soil sample from Lippo Cikarang is in the category of high development potential; The stability of the subgrade soil as part of the road body is given by the CBR value, the stability in the study with 5 layers, the formation is soil + sand + soil + sand + soil, with a geotextile layer (G1) of 14.9%, G2 of 16.85%, and G3 by 10.73%, and G4 formation by 6.53%. The magnitude of stability (CBR) and expansion of the expansive soil from Lippo Cikarang which was compacted according to the Modified Compaction was 5.45% (original soil), while the swelling was 12.7 %; The provision of geotextile membranes for the G3 and G4 formations has a positive effect, namely swelling below the original soil swelling value so that it provides development below the original soil value.